A Laboratory Model for a Meandering Zonal Jet. (30th June 2022) - Stewart, K. D.; Macleod, F.
Abstract: The meandering jet streams of the Northern Hemisphere influence the weather for more than half of Earth's population, so it is imperative that we improve our understanding of their behavior and how they respond to climate change. Here, we describe a novel laboratory model for a meandering zonal jet. This model comprises a large rotating annulus with a series of topographic ridges, and an imposed radial vorticity flux. Flow interactions with the topographic ridges operate to concentrate the zonal transport into a narrow jet, which supports the development and propagation of Rossby waves. We investigate the dynamics of the jet for a range of rotation rates, imposed radial vorticity fluxes, and topographic ridge configurations. The circulations are classified into two distinct regimes: predominantly zonal or predominantly meandering. The flow regime can be quantified by the ratio of the Ekman dissipation and jet advection timescales, which gives an indication of whether disturbances arising from the flow‐topography interaction are dissipated faster than the time taken to circuit the annulus; if not, these disturbances will reencounter the topography, and thus be reinforced and amplified. For predominantly zonal flows, the radial vorticity flux is split equally between the standing meanders and transient eddies. For predominantly meandering flows, standing meanders perform 79% of the radial vorticity flux, with 18% accommodated by the transient eddies. Our experiments indicate that the Arctic amplification associated with climate change will tend to favor predominantly zonal flow conditions, suggesting a reduced occurrence of atmospheric blocking events caused by the jet streams. Plain Language Summary: Jet streams are narrow, meandering bands of intense eastward winds circling Earth in the upper atmosphere. They are a prominent dynamical feature of Earth's climate system and have major implications for navigation and weather prediction. Modeling the jet streams is important for understanding their dynamics and how they might be affected by climate change. Here, we describe a new approach for laboratory experiments to model meandering jets like the jet streams. The laboratory circulations can be classified into two distinct flow states: one which is predominantly eastward or one which has substantial north‐south meanders in addition to its eastward flow. The flow state of a particular experiment is shown to depend on the relative strength of the forcing and the rate at which the jet variability is dissipated. Key Points: We use a novel laboratory experiment to investigate zonal jet dynamics and distinguish between standing meanders and transient eddies Flows occupy two distinct regimes; predominantly zonal, or predominantly meandering, depending on the timescales of forcing and dissipation For predominantly meandering flow, the standing meanders perform 79% of meridional tracer transport, with 18% by transient eddies